APA dictionary of clinical psychology - VandenBos, Gary R.; American Psychological Association (Washington, DC : American Psychological Association, 2013)
APA dictionary of clinical psychology : 11, 000 entries offering clear and authoritative definitions ; Balanced coverage across core areas-including assessment, evaluation, diagnosis, prevention, and treatment of emotional and behavioral disorders; training and supervision; as well as terms more generally relevant to the biological, cognitive, developmental, and personality/social psychological underpainnings of mental health ; Hundreds of incisive cross-references to deepen the user's understanding of related topics ; A Quick guide to use that explains stylistic and formal features at a glance ; Appendixes listing major figures relevant in the history of clinical psychology and psychological therapies and psychotherapeutic approaches.
Keywords: Clinical psychology -- Dictionaries; Psychotherapy -- Dictionaries